1981
DOI: 10.1093/ajcn/34.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin A fortification of sugar on the serum vitamin A levels of preschool Guatemalan children: a longitudinal evaluation

Abstract: Based on the Guatemalan program of vitamin A fortification of sugar, a longitudinal evaluation on serum retinol levels of preschool-aged children was performed. Five consecutive surveys executed every 6 months were examined, considering only children who were surveyed more than once. Thus, the changes in their serum retinol after the intervention were evaluated. Natural dietary vitamin A remained unchanged throughout. Addition of retinyl palmitate to sugar increased significantly the intake (p < 0.001). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 10 publications
0
61
0
1
Order By: Relevance
“…32,33 Costa Rica and El Salvador also had improvements in vitamin A status, presumably as a consequence of the implementation of national sugar fortification programs. 12,14,33 On the other hand, an increase in the prevalence of vitamin A deficiency was observed in the only two South American countries where data were collected before and after 1998 (Ecuador and Colombia). The highest rates of deficiency in these two countries are found among the most disadvantaged and economically vulnerable groups, indigenous people and people of African descent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Costa Rica and El Salvador also had improvements in vitamin A status, presumably as a consequence of the implementation of national sugar fortification programs. 12,14,33 On the other hand, an increase in the prevalence of vitamin A deficiency was observed in the only two South American countries where data were collected before and after 1998 (Ecuador and Colombia). The highest rates of deficiency in these two countries are found among the most disadvantaged and economically vulnerable groups, indigenous people and people of African descent.…”
Section: Discussionmentioning
confidence: 99%
“…In Guatemala, the introduction of fortification of sugar with retinyl palmitate in 1975 resulted in a substantial increase in vitamin A status one year after the program's implementation. 12 El Salvador, Honduras, and Nicaragua later implemented national sugar fortification programs because of its cost-effectiveness. 33 As shown by the most recent surveys, Guatemala (prevalence 0.3% in 2010, a decrease of 15.5 percentage points from 1995) and Nicaragua (prevalence 0.7% in 2005, a decrease of 30.3 percentage points from 1993) essentially eliminated vitamin A deficiency; El Salvador was the country with the highest reduction in prevalence, with a decrease of 31.0 percentage points.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, food fortification to combat vitamin A deficiency seems preferable for the current situation. Some studies have shown that fortification of condiments such as monosodium glutamate 29 , sugar 30 and wheat 31 with vitamin A considerably improved vitamin A status. However, vitamin A-fortified monosodium glutamate in Indonesia was not favourable since it changed the colour and increased the price of the product.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of fortification and capsule distribution would be more effective 59 . Sugar 60 or cookies 60,62 fortification led to an increase in vitamin A and plasmatic retinol levels in children, especially in those whose basal levels were below 20µg/dl 60,61 , reducing the percentage of children with inadequate liver vitamin A reserves 61,63 . The fortification of cookies with β-carotene at a level of 50% of the RDA was sufficient to maintain the concentration of plasmatic retinol on a daily basis, but not during long vacation periods, in primary school children 62 .…”
Section: The Nutritional Importance Of Fortified Foods Vitamin Amentioning
confidence: 99%